An Assessment of soil Fertility Management Issues in Pokhare Khola Watershed, Dhading - Pandit, K.; Balla, M. K. (Nepal Journal of Science and Technology, 2007)
Changes in traditional ways of cropping and fertility maintenance have posed a serious threat of the sustainability of soil fertility in the mid hills of Nepal. This paper tries to bring to the front different issues directly or indirectly related to the sustainability of soil fertility based on a study carried out in Pokhare Khola Watershed, Dhading in 2003. Data were collected through questionnaire survey and focus group discussions and interpretation made using simple statistical tools and logical discussions. Cultivation of short growing season varieties of crops supplemented with high rates of chemical fertilizers has substantially increased the cropping intensity in irrigated low land. Farm yard manure (FYM) is used in higher proportion than chemical fertilizers both in Khet (irrigated lowland) and Bari (non-irrigated upland). Nonetheless, Khet land gets lower amount of FYM and higher amount of chemical fertilizers compared to Bari. Farmers are practicing the traditional methods of preparing FYM. Erosion in Bari and sedimentation in Khet lands are the major threats to soil fertility but no adequate prevention and restoration measures are carried out to cope with these threats. Farmers have not only conserved natural forests but also, planted fodder trees in their farmlands. Nearly half of demand for forest products is met from private farmland, which has considerably reduced the pressure on nearby forests. Farmers have markedly positive perceptions regarding the fertilizer application, cropping pattern and importance of forests in farming system. Nepal Journal of Science and Technology Vol. 7, 2006